Analysis of the Ability to Understand Mathematical Concepts Based on Student Learning Styles in Calculus Courses - Nawafilah, Nur Qomariyah; Masruroh, Masruroh (Tarbiyah : Jurnal Ilmiah Kependidikan, 2024)
Understanding mathematical concepts can make a person's understanding of mathematics more complex. However, in reality, students memorize mathematics without developing a strong understanding of the concept. On the other hand, learning style is a student's way of processing the information obtained to build an understanding of mathematical concepts. Based on these two things, this research analyzes students' ability to understand mathematical concepts in solving calculus-related problems by considering learning styles, such as visual, auditory, or kinesthetic. The research method used is descriptive qualitative. The research subjects were students in the first semester of the Informatics Engineering Department at Universitas Islam Lamongan. Data was collected by using questionnaires, tests, and interviews. The research results show that students with auditory, visual, and kinesthetic learning styles are categorized as very good on the indicator of restating concepts, with an average of 84%, 92%, and 81%. Students with an auditory learning style are categorized as very good in presenting examples and non-examples, averaging 72%. Visual and kinesthetic are categorized as good, averaging 64% and 67%. For indicators connecting various concepts, students with auditory and visual learning styles are categorized as poor, with an average of 38% and 36%. In contrast, kinesthetics are categorized as good, with an average of 55%.